The current situation and strategy of Olympic education for primary and secondary school students based on Science- Technology- Engineering- Art- Mathematics education in the context of physical literacy - Li, Jia; Yuan, Lei (Frontiers in Psychology, 2022)
The purpose of this paper is the influence of Science- Technology- Engineering- Art- Mathematics (STEAM) education on the Olympic education of primary and middle school students. The research object is the Beijing Olympic model school. The frame structure and educational concept of STEAM education are studied, and a questionnaire survey on the current situation of Olympic education is conducted. Finally, improvement measures based on the survey results are provided combined with STEAM education, and the teaching effect is analyzed. The results show that after the improvement of the educational model, the student’s mastery of the Olympic knowledge has been greatly improved. The proportion of students who can master all knowledge increases from 5.78% to 8.45%, by 2.67%. The proportion of students with knowledge of most Olympic sports increases from 48.6% to 55.67%, by 7.07%. The proportion of students with little or no knowledge drops to 1.54%. Meanwhile, students are increasingly interested in Olympic events, especially after being inspired by the STEAM education model. The proportion of students who are very concerned about Olympic events has increased by 6.45%. The proportion of students who are more concerned about Olympic events has increased by 5.11%. Thus, the Olympic education work has achieved some results. Students gradually become interested in the Olympic events. They begin to actively pay attention to the Olympic events and learn the Olympic spirit. Then, their physical literacy is improved.